Performance Evaluation of Bajaj Boll Opener for Cleaning and Opening of kawdi Cotton in Ginneries - GHADGE, S. V.; SHUKLA, S. K.; SATANKAR, V.; PATIL, D. U.; SHIRSATH, B. V. (Cotton Research Journal, 2021)
India is the leading cotton producing country in the world with production of about 20 m t of seed cotton harvested every year. The harvested seed cotton contains dust particles, leaves, and immature and unopened cotton bolls, called kawdi cotton for resemblance to kawdi sea shells. When raw seed cotton is taken to ginneries, it is passed through many cleaning systems like hot-box dispenser and pre-cleaner where kawdi cotton is removed. If seed cotton is infested by insect attack or improper production technology, significant amount of kawdi cotton is present in it. About 5-25% kawdi cotton is expected in ginneries depending on the extent of infestation and damage. This material is generally ignored by ginners considering it as a waste material. However, it can be processed and good quality lint can be recovered from it that can provide additional income to ginners. Difficulties in processing kawdi cotton are causing ginners huge losses. If this material is cleaned, opened and ginned, a ginner can make about 1000 bales in a single season and earn an additional profit of around Rs. 2 crore from it. Though, research on processing of kawdi cotton is scant with no reported past data, machines like ‘Bajaj Boll Opener’ are available in the market for cleaning and opening of kawdi cotton, selected for performance evaluation in this study. It was found that the machine could process kawdi cotton at about 1.0 t per h capacity with 40% recovery of ginnable seed cotton. The ginning trials and fibre quality analysis revealed that good quality lint could be obtained from the opened kawdi cotton, thus yielding additional profit to ginners.